Ten Year Evaluation of JKN: Strengthening Primary Health Care for National Resilience - Silalahi, Verry Albert Jekson Mardame (Indonesian Journal of Economic & Management Sciences, 2024)
This study evaluates the achievements of the National Health Insurance (JKN) over the past ten years, focusing on strengthening primary healthcare for national health system resilience. Launched on January 1, 2014, JKN aims for equitable healthcare access for all Indonesians, with participants reaching over 220 million by 2023. JKN has increased basic health service coverage, including immunization, maternal and child care, and treatment of diseases. Primary healthcare's role is vital in disease prevention, early diagnosis, treatment, and chronic disease management. Case studies highlight successful outreach programs. Challenges include funding deficits, uneven service quality, and lack of medical personnel in remote areas. Recommendations include increased budget allocations, incentive policies, continuous training, integration of services, effective health information systems, and community participation